2006
DOI: 10.1159/000095558
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of Classical Hodgkin Lymphoma

Abstract: The World Health Organization has acknowledged the malignant nature of classical Hodgkin lymphoma (cHL), which encompasses four histological subtypes. The diagnosis of cHL is based on the detection of malignant Hodgkin and Reed-Sternberg cells (HRSC) confirmed by immunophenotyping and the detection of growth patterns specific to each histological subtype. The pathologic HRSC arise from germinal center or immediate postgerminal cells that lack detectable immunoglobulin/B-cell antigen receptor expression, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 255 publications
(181 reference statements)
1
38
0
2
Order By: Relevance
“…Hodgkin and Reed-Sternberg cells are known for their defective cell cycle and apoptosis regulation, which enables them to escape therapy (reviewed in ref. 7), a theory which is supported by our finding of clonally related recurrences. Another hypothesis focuses on the existence of tumor stem cells in HL.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Hodgkin and Reed-Sternberg cells are known for their defective cell cycle and apoptosis regulation, which enables them to escape therapy (reviewed in ref. 7), a theory which is supported by our finding of clonally related recurrences. Another hypothesis focuses on the existence of tumor stem cells in HL.…”
Section: Discussionsupporting
confidence: 82%
“…3, 11, 14, 15, and 20), and late recurrences in 17 patients (no. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In 1 case (no.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…8-11 Importantly, the transforming lymphomagenesis events in both FL and cHL probably occur during the socalled germinal center (GC) reaction, 12,13 which is the most important step in B-cell maturation during T-cell dependent antigen responses.…”
Section: Introductionmentioning
confidence: 99%
“…Although HL in general has a favorable prognosis but more molecular studies are required for the refractory and relapsed patients [9][10][11][12] to discover the unresolved molecular pathobiological issues of HL [2,13,14]. Recently, advances in molecular profiling of HRS cells have shown that this small number of malignant cells have a potential role in the HL pathogenesis through different pathways like providing a typical microenvironment by secretion of cytokines and chemokines (CCL5, CCL17, CCL22, IL5, TGF-β, PDGF, IL2, IL6 [2,4,15], deregulating of transcription factor network [2], and escaping from apoptosis [13,15,16].…”
Section: Introductionmentioning
confidence: 99%